Liquid Smoke from Coconut Shell Pyrolysis Process on Palm Surfactant Based Liquid Hand Soap - Shafira Nurfadhila; Erliza Hambali (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2022)
The use of synthetic antibacterial liquid hand soap such as triclosan has begun to be avoided. Therefore it is necessary to find an antibacterial alternative that is safe for the skin and friendly to the environment. One of the environmentally friendly antibacterial alternatives is liquid smoke resulting from the pyrolysis process from coconut shells. The purpose of this study was to obtain the right concentration of liquid smoke for liquid hand soap made from palm MES surfactants and glycerol. The stages of the research were raw material analysis, liquid soap formulation (surfactant methyl ester sulfonate 7.5%, surfactant diethanolamide 5%, palm glycerol 9%, sodium chloride 1%, liquid smoke grade I, and distilled water). The treatments in this study were the addition of 1, 3, and 5% grade I liquid smoke. The next stage is an analysis of the physicochemical properties of the resulting liquid soap product, quality test was carried out based on SNI 2588: 2017, and a product effectiveness test. Liquid soap with the addition of 1% liquid smoke showed the best results with a density value of 1.037 g cm-3, specific gravity 1.04, viscosity 11,560 cP, surface tension 29.08 dyne cm-1, pH 7.2, free fatty acids 0.27%, ingredients insoluble in ethanol 0.14%, the total active ingredient is 12.52%, the number of plates is 990 CFU g-1, the colony reduction is 61.13%, and has the minimal pungent aroma.